Advances in conceptual modeling : ER 2017 Workshops AHA, MoBiD, MREBA, OntoCom, and QMMQ, Valencia, Spain, November 6-9, 2017, Proceedings /: ER 2017 Workshops AHA, MoBiD, MREBA, OntoCom, and QMMQ, Valencia, Spain, November 6-9, 2017, Proceedings. (2017) - Unknown
No abstract available